86.4k views
5 votes
The explicit rule for a sequence is an=7(−4)n−1

.



What is the recursive rule for the sequence?


an=−4(an−1),a1=7
an=−7(an−1),a1=4
an=−7(an+1),a1=4
an=−4(an+1),a1=7

User Ian Kemp
by
5.5k points

2 Answers

1 vote

Answer:

Option (a) is correct.

The recursive rule for the given sequence
a_n=7(-4)^(n-1) is
a_n = (-4)\cdot a_(n-1) with
a_1=7

Explanation:

The explicit sequence of the geometric sequence is given by:


a_n = a_1r^(n-1)

where,


a_1 is the first term

r is the common ratio

n is the number of terms

For the given explicit rule,
a_n=7(-4)^(n-1)

Comparing with above sequence , we have,


a_1=7 and r = -4

Recursive formula for the geometric sequence having
a_1=7 and r = -4 is given by:


a_n=r\cdot a_(n-1) \ for\ n\geq 2

Putting values, we get,


a_n = (-4)\cdot a_(n-1)

Hence, the recursive rule for the given sequence
a_n=7(-4)^(n-1) is
a_n = (-4)\cdot a_(n-1) with
a_1=7

hence, option (a) is correct.

User ThMore
by
5.7k points
2 votes
The correct answer is


a_n=-4(a_(n-1)), a_1=7

The explicit formula is of the form

a_n=a_1(r)^(n-1),
where a₁ is the first term and r is the common ratio. Comparing this to our explicit form, we see that r = -4 and a₁ = 7.

The recursive formula is of the form

a_n=a_(n-1)*r; using r=-4 gives us

a_n=-4(a_(n-1)), a_1=7
User Luca Taccagni
by
6.4k points